Retrospective study of non-neoplastic cytological diagnoses of dogs and cats in an animal pathology laboratory from 2010 to 2020 (Research, Society and Development, 2023)
Cytological examination is a simple method that provides important information for diagnosis, treatment, control and prevention measures. This study aimed to determine the prevalence of non-neoplastic cytological diagnoses in dogs and cats in the region of Araçatuba, São Paulo (SP), carried out by the Veterinary Pathology Sector (SPV) of the Faculty of Veterinary Medicine of Araçatuba/SP (FMVA) from the São Paulo State University "Júlio de Mesquita Filho" (UNESP), from 2010 to 2020. There were 13,037 cytological diagnoses from 8,868 animals, most of which were dogs 8,395 (94.66%) and 473 (5.34% ) cats. Females in both species were more prevalent with 5,464 (61.61%) animals and the mean age in dogs was 85.36 months (7 years) and for cats 81.18 months (6.7 years). The most prevalent breed in dogs and cats were mixed breed animals (SRD). A total of 8,696 non-neoplastic cytological diagnoses were classified in dogs and cats, with non-inflammatory diagnoses being the most prevalent with 3,692 (42.46%) diagnoses, followed by inconclusive ones with 2,186 (25.14%), 1,622 (18.65%) diagnoses. infectious, 964 (11.09%) inflammatory and 232 (2.67%) diagnoses without change. In dogs the non-inflammatory cytological diagnoses were the most prevalent with 3,630 (43.77%), in cats the inflammatory ones with 111 (27.54%). The pelvic limbs were the anatomical location with the highest number of cytological diagnoses in dogs with 2,323 (28.01%) and in cats the head with 185 (45.90%).